The Pilgrimage Tourism Importance In The Socio-Economic Relations Development (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article highlights the important tourism role, especially pilgrimage tourism, in the socio-economic relations development. There is information about the attention paid to the tourism sector in our country, the laws and decisions being adopted, their practical significance. There are comments on the religious pilgrimage tourism development, increasing its role in the socio-economic relations development.